2022
DOI: 10.1002/tesq.3144
|View full text |Cite
|
Sign up to set email alerts
|

Assisting and Mediating Interaction during Synchronous Online Language Lessons: Teachers' Professional Practices

Abstract: Synchronous online language lessons (SOLLs) are distinctly different from in-person lessons. Although digital tools, specifically, videoconferencing software, make doing SOLLs possible, these tools have specific affordances and constraints pertaining to how we engage, interact, and relatecreating new literacy practices. This study reports on a project which explored how five Hong Kong university English language teachers engaged in teaching SOLLs over a 13-week semester. The aim of the project was to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Another two recommendations are related to strengthening the quality of consultant-writer interactions. First, while appreciating the strengths of VCS, consultants may need to be sensitised to some potential interactional issues with web-based tutoring and some skills for facilitating online interactions (Moorhouse et al, 2021(Moorhouse et al, , 2022Rehn et al, 2018), including but not limited to pacing and maximising writers' talk via, for instance, asking softball questions to check their understanding and presence in the consultations, especially when writers choose to turn off their web cameras. Related to this recommendation, a further suggestion, made by Consultant Carmen, is to create a list of 'Frequently Asked Questions' that outlines the common issues with synchronous virtual writing and ways used by other consultants to overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another two recommendations are related to strengthening the quality of consultant-writer interactions. First, while appreciating the strengths of VCS, consultants may need to be sensitised to some potential interactional issues with web-based tutoring and some skills for facilitating online interactions (Moorhouse et al, 2021(Moorhouse et al, , 2022Rehn et al, 2018), including but not limited to pacing and maximising writers' talk via, for instance, asking softball questions to check their understanding and presence in the consultations, especially when writers choose to turn off their web cameras. Related to this recommendation, a further suggestion, made by Consultant Carmen, is to create a list of 'Frequently Asked Questions' that outlines the common issues with synchronous virtual writing and ways used by other consultants to overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this recommendation, a further suggestion, made by Consultant Carmen, is to create a list of 'Frequently Asked Questions' that outlines the common issues with synchronous virtual writing and ways used by other consultants to overcome these challenges. Second, writers could be reminded of the 'netiquette' as well as the affordances and constraints of videoconferencing (Moorhouse et al, 2021(Moorhouse et al, , 2022, such as staying in a non-distracting environment with stable Internet connection (Andersson & Nakahashi, 2019), giving constant verbal and non-verbal feedback to their consultants, and participating respectfully in the consultations which are still a form of institutional talk between a member of the university writing centre and a student.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of research has examined emergency remote teaching practices in English language teaching (ELT), including the use of VCS such as Zoom (see Moorhouse and Kohnke (2021) for an early systematic review of the literature). ELT research into the use of VCS in emergency remote teaching has shown how teachers had to develop technological competences, online environment management competences and online interactional competences to facilitate e-classroom interaction (Moorhouse et al, 2021; Moorhouse et al, 2022). Such research has documented a range of pedagogical and interactional strategies that teachers used in synchronous online language lessons.…”
Section: Language Learning During the Pandemicmentioning
confidence: 99%
“…Apart from the mobility feature, a positive classroom climate featuring these technologies is marked by the possibility of incorporating multiple media (different sources of audio-visual and textual information), which facilitates more effective teacherlearner and learner-learner interactions (Traxler, 2009;Manegre and Sabiri, 2022;Moorhouse et al, 2022). The multimedia-laden L2 classroom climate has led to the development of an interactive course content and cooperative learning tasks to complete in several settings.…”
Section: Implications Of Positive Classroom Climate For Online L2 Cla...mentioning
confidence: 99%